(untitled) (International Journal of Engineering and Computer Science, 2013)
The corrosion inhibition of oil well tubular steel(N-80 steel) in well acidizing solution (15% Hydrochloric acid) by extract of Ficus Abutilifolia (FA) was studied using weight loss technique. Maximum inhibition efficiency (and surface coverage) was obtained at an optimum concentration. However, increase in temperature decreased the inhibition efficiency at the temperature range studied. The inhibition efficiencies were compared to a standard oil well acidization corrosion inhibitor, Propargyl Alcohol. Optimum inhibition efficiency for the tubular steel in the presence of Ficus Abutilifolia were 57.40% at 60oC and 52.57% at 90oC while those for Propargyl Alcohol were 90.97% at 60oC and 67.50% at 90oC. The phenomenon of physical adsorption has been proposed from the heat of adsorption values of all inhibitors studied (-9.35686 to -2.65846kJ/mol). Activation energy values indicates a surface reaction.